CuAAC Synthesis of Tetragonal Building Blocks Decorated with Nucleobases - Pop, Lidia; Golban, Mirabela Ligia; Hădade, Niculina D.; Socaci, Crina; Grosu, Ion (Synthesis, 2015)
The CuAAC synthesis and the characterization of new rigid nucleobase-decorated tetrapodands exhibiting 1,3,5,7-tetraphenyladamantane and 9,9′-spirobifluorene central units are reported. 1,3,5,7-Tetraphenyladamantane and 3,3′,6,6′-tetrasubstituted 9,9′-spirobifluorene derivatives are tetrahedral building blocks, while the derivatives of 2,2′,7,7′-tetrasubstituted 9,9′-spirobifluorene can lead to 2D architectures.
Keywords: ‘click’ chemistry; nucleobase-decorated building blocks; tetrapodands; tetraphenyladamantane; 9,9′-spirobifluorene